The peace index : a five-part framework to conquer chaos and find fulfillment - Kubicek, Jeremie (John Wiley & Sons, Inc., 2023)
"The Peace Index provides a framework to help people find sustained balance in their lives. It is comprised of five parts: purpose, people, place, personal health, and provision. Each part informs a person's overall wellbeing and happiness. To calculate your peace index, you assign a number between 1-100 to each part. For example, if you assign your purpose a 70, that indicates you need to rediscover what drives your life. If you assign people a 95, you're deeply fulfilled by the people in your life. Your peace index score is the total of all 5 parts divided by 5. Completing this exercise helps you easily identify the parts of your life that are strong and the parts that need work. The Peace Index will be structured around these five parts and expound on each component to guide you towards more equilibrium in your life"--